2016
DOI: 10.1590/s0100-83582016340400007
|View full text |Cite
|
Sign up to set email alerts
|

Management of Ascochyta rabiei by Chenopodium album Extracts

Abstract: -Chenopodium album, leaves were selected to evaluate their antifungal potential against Ascochyta rabiei causative agent for chickpea blight. Different concentrations of methanolic extract of C. album leaves i.e. 1%, 2.5%, 4%, 5.5% and 7% were tested against the target fungus A. rabiei. Maximum reduction in the test fungal biomass (68%) was observed in 7% concentration. This methanolic leaf extract was partitioned and n-butanol, chloroform, n-hexane, ethyl acetate fractions were isolated according to their pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
(6 reference statements)
1
9
0
Order By: Relevance
“…Increasing evidences have shown that natural products can be useful to reach a proper biological control of plant pests, attributed to the presence of several secondary metabolites, which control the disease up to an extent. Plant-derived phytochemicals, like saponins, alkaloids, terpenoids, flavonoids, tannins, and cardiac glycosides, have shown excellent antifungal properties against pathogenic fungi [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidences have shown that natural products can be useful to reach a proper biological control of plant pests, attributed to the presence of several secondary metabolites, which control the disease up to an extent. Plant-derived phytochemicals, like saponins, alkaloids, terpenoids, flavonoids, tannins, and cardiac glycosides, have shown excellent antifungal properties against pathogenic fungi [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Various concentrations (1-7%) of methanolic extracts were prepared and checked against A. rabiei. 7% concentration exhibited strong antifungal activity up to 68% against test fungus [8]. It was reported that antimicrobial property of C. album was due to presence of saponins, flavonoids, alkaloids, phenolics, ascorbic acids, calcium, phosphate, minerals, salts, and protein [12].…”
Section: Introductionmentioning
confidence: 99%
“…Various concentration viz. 1%, 2%, 3%, 4% and 5% of methanolic extract were prepared in 2% MEA medium (Sherazi et al, 2016). The control treatment was without any plant extract.…”
Section: Methodsmentioning
confidence: 99%
“…Mass detector conditions were: ionization voltage 70 eV mass scanning range m/z 29-540 and source temperature 230 o C. The percentage composition of volatile compounds was computed from GC peak areas. Qualitative analysis was based on a comparison of retention times, indices and mass spectra with the corresponding data in the literature (NIST Library 2010 word software) (Sherazi et al, 2016) All the data were statistically analyzed by using analysis of variance (ANOVA) followed by Duncan's Multiple Range test (DMR) at Pd"0.05 (Steel et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…This partitioning resulted in the gummy mass of n-hexane (1.56 g), chloroform (2.66 g), ethyl acetate (2.23 g) and n-butanol (1.86 g). All the four fractions were serially diluted to check their bioactivity against the target fungus by following the protocol of Sherazi et al (2016).…”
Section: In Vitro Bioassay With Isolated Fractionsmentioning
confidence: 99%